Influência do leite com elevada contagem de células somáticas sobre características físico-químicas e processo de fermentação de iogurte - Alana Paula Amaral Faria (2016)
The objective of this study was to evaluate characteristics of yogurts made with high and low Somatic Cell Count (CCS) milk. Raw milk samples were collected on six different days and were submitted to electronic analyzes of protein, fat, lactose, total solids, CCS and total bacterial count (CBT). The fermentation process was monitored through pH and acidity expressed as lactic acid. The yoghurts were analyzed for pH, acidity expressed in lactic acid, and syneresis of the final product, at different storage times. The experiment was conducted in a randomized block design (DBC), with six replications and split plot, with the plots treatments (1 - yogurt, up to 250.000 CS / mL; 2- enriched with solids yogurt, up to 250.000 CS / mL; 3- yoghurt, more than 250.000 CS / mL and 4-enriched with solids yogurt, more than 250.000 CS / mL) and subplots fermentation times and storage periods for yoghurts. The data were submitted to analysis of variance (ANOVA) and regression analysis according to the times of measures on fermentation profile and yoghurts storage time. Parameters of milk composition were still submitted to correlation index. The results showed effects of CCS levels on some milk parameters (p<0,05). However, no effects were observed on fermentation profile and characteristics of yoghurts along the storage.